2019
DOI: 10.1108/josm-07-2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging service design as a multidisciplinary approach to service innovation

Abstract: Purpose Service design is a multidisciplinary approach that plays a key role in fostering service innovation. However, the lack of a comprehensive understanding of its multiple perspectives hampers this potential to be realized. Through an activity theory lens, the purpose of this paper is to examine core areas that inform service design, identifying shared concerns and complementary contributions. Design/methodology/approach The study involved a literature review in two stages, followed by a qualitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 95 publications
(139 reference statements)
0
29
0
2
Order By: Relevance
“…However, as noted by the interviewees, strategic resources were only able to provide for enhanced performance and sustained business competitiveness where they are leveraged. Interestingly, the reality that the existence of VIRO attributes within resources is not sufficient to create enhanced performance and sustained business competitiveness resonates with existing works of literature (see Bingham and Eisenhardt 2008;Combs et al 2011;Zollo, Minoja, and Coda 2018;Prestes Joly et al 2019). Instead, such performance and competitiveness stem from a combination of factors which includes (i) an appreciation of VIRO resources, (ii) an appreciation of non-VIRO resources (iii) an understanding of how the underlying characteristics of both VIRO and non-VIRO resources impact upon their relationships and (iv) the ability of the organization to identify, develop, and exploit resource complementarity in a manner that ensures the effective and efficient transfer of resources across various levels of the organization.…”
Section: Discussionmentioning
confidence: 63%
“…However, as noted by the interviewees, strategic resources were only able to provide for enhanced performance and sustained business competitiveness where they are leveraged. Interestingly, the reality that the existence of VIRO attributes within resources is not sufficient to create enhanced performance and sustained business competitiveness resonates with existing works of literature (see Bingham and Eisenhardt 2008;Combs et al 2011;Zollo, Minoja, and Coda 2018;Prestes Joly et al 2019). Instead, such performance and competitiveness stem from a combination of factors which includes (i) an appreciation of VIRO resources, (ii) an appreciation of non-VIRO resources (iii) an understanding of how the underlying characteristics of both VIRO and non-VIRO resources impact upon their relationships and (iv) the ability of the organization to identify, develop, and exploit resource complementarity in a manner that ensures the effective and efficient transfer of resources across various levels of the organization.…”
Section: Discussionmentioning
confidence: 63%
“…Service design can be perceived in a multidisciplinary approach bringing service innovation either by creating new services or enhancing existing services [29]. This is manifested through understanding user experience, rethinking value proposition, and welcoming technological revolution resulting in a new service delivery process.…”
Section: Service Designmentioning
confidence: 99%
“…It is against this background the SD approach is recognized as a catalyst for both organizational and service transformation (Malmberg, et al, 2019). In their study to examine the core areas that inform SD research (SDR), Joly et al (2019) identified IS, which is related to IT as one among six dimensions that have been recognized to offer support and enablement of service innovation. In this case, therefore, the SD strategy becomes a key context for applying ICT, which digitizes information interactions in service to facilitate value creation which subsequently contributes to service innovation (Patrício, de Pinho, Teixeira, & Fisk, 2018;Lim, et al, 2018).…”
Section: The Service Design Conceptmentioning
confidence: 99%